A Memory-Type Porous Thermoelastic System With Microtemperatures Effects and Delay Term in the Internal Feedback: Well-Posedness, Stability and Numerical Results - Chabekh, Meriem; Chougui, Nadhir; Yazid, Fares; Saadallah, Abdelkader (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we consider a one-dimensional porous thermoelastic system with microtemperatures effects, past history term acting only on the porous equation and a delay term in the internal feedback. Under an appropriate assumptions on the kernel and between the weight of the delay and the weight of the damping, we prove the well-posedness of the system. Furthermore, we establish a general decay rate result for the energy, which allows a wider class of relaxation functions, and thus generalize some results in the literature. Finally, some numerical experiments are presented.